ANALISIS MANAJEMEN LABA PADA SAAT INITIAL PUBLIC OFFERINGS (IPO): INDIKASI SIKAP OPORTUNISTIK MANAJEMEN - Susilawati, R. Anastasia Endang (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2011)
The purpose of this analysis is to: (1) look for the empirical proof if the earning management is opportunistic, so discretionary accruals to IPO period will predict the decrease of kinergy on pasca period of IPO; (2) look for the empirical proof whether the decrease of issuer kinergy is bigger than matched-pair because of doing earning management. This analysis used issuer data in the period of 2004-2005, there were 30 issuers and matched-pair. The methodology is as done by Teoh et al. (1998a). The result of the analysis shows that the go public company’s managers are opportunistic by doing earning management to fix the kinergy, it is proved by positive point of discretionary accruals on offering period. The positive point of discretionary accruals indicates that earning management which has been done by the managers are income increasing. Another invention indicates that issuers do earning management more aggresively than matched-pair, and in long period earning management which has been done by the manager could not be continued, so that the company will get the decrease of kinergy on pasca IPO